AB0788 Differences in the phenotypic expression of recent onset psoriatic arthritis among men and women: baseline data from the reapser study. (15th June 2017) - Queiro, R; Alonso, A Laiz; Park, HS; Morales, C Montilla; Agirregoikoa, E Galíndez; Baute, JJ Bethencourt; Reyes, S Bustabad; Tejόn, P Menéndez; Belmonte, MΆ; Tasende, JA Pinto; Morales, E Alonso Blanco; Ramír, J
Abstract : Background: The natural history of psoriatic arthritis (PsA) according to gender of patients is an aspect of the disease only partially studied. In prospective PsA cohorts such information is barely known. Objectives: To analyze baseline gender differences in the REAPSER cohort (Psoriatic Arthritis Registry of the Spanish Society of Rheumatology). Methods: Observational, multicenter study (34 centers), with consecutive inclusion. We included adults of both sexes 18 years of age or older with PsA that met CASPAR criteria, and duration of less than two years since the appearance of symptoms attributed to PsA. Annual follow-up visits will be carried out for 5 years. Measurements: socio-demographic data; employment status and impact of the disease; family history of PsA and other inflammatory diseases; comorbidities and treatment; lifestyle; use of health services; clinical status at the time of diagnosis of PsA; anthropometric data; clinical evaluation of PsA manifestations; radiographic evaluation; analytical determinations; treatment of PsA. The study has been approved by the Ethical committees of the participating centers. Comparative statistical analysis: for qualitative variables, the χ-square or the Fisher exact statistic were used. For non-normal quantitative variables, non-parametric tests were used and for normal quantitative variables, Student's t-test was used. Results: The results are expressed in the table. Conclusions: The baseline data from this prospective cohort point to significant differences in the phenotypic expression of PsA between men and women. Thus, in women, the prevalence of dactylitis and pustular psoriasis was higher, there were higher rates of depression and a perception of higher disease activity. Women scored higher on the pain linked to their arthritis and the activity of axial disease. They also had biological activity parameters (ESR) higher than that of men. It is necessary to determine if these differences are maintained or change over time. Disclosure of Interest: None declared